Probiotics and Their Potential Preventive and Therapeutic Role for Cancer, High Serum Cholesterol, and Allergic and HIV Diseases. (29th August 2018) - Nazir, Yusuf; Hussain, Syed Ammar; Abdul Hamid, Aidil; Song, Yuanda
Abstract : The potential health benefits of probiotics have long been elucidated since Metchnikoff and his coworkers postulated the association of probiotic consumption on human's health and longevity. Since then, many scientific findings and research have further established the correlation of probiotic and gut-associated diseases such as irritable bowel disease and chronic and antibiotic-associated diarrhea. However, the beneficial impact of probiotic is not limited to the gut-associated diseases alone, but also in different acute and chronic infectious diseases. This is due to the fact that probiotics are able to modify the intestinal microbial ecosystem, enhance the gut barrier function, provide competitive adherence to the mucosa and epithelium, produce antimicrobial substances, and modulate the immune activity by enhancing the innate and adaptive immune response. Nevertheless, the current literature with respect to the association of probiotic and cancer, high serum cholesterol, and allergic and HIV diseases are still scarce and controversial. Therefore, in the present work, we reviewed the potential preventive and therapeutic role of probiotics for cancer, high serum cholesterol, and allergic and HIV diseases as well as providing its possible mechanism of actions.